The endocannabinoid system in zebrafish and its potential to study the effects of Cannabis in humans - Ricardo Lacava Bailone; Hirla Costa Silva Fukushima; Luis Kluwe de Aguiar; Ricardo Carneiro Borra (Laboratory Animal Research, 2022)
Abstract Zebrafish is considered an unprecedented animal model in drug discovery. A review of the literature presents highlights and elucidates the biological effects of chemical components found in Cannabis sativa. Particular attention is paid to endocannabinoid system (eCB) and its main receptors (CB1 and CB2). The zebrafish model is a promising one for the study of cannabinoids because of the many similarities to the human system. Despite the recent advances on the eCB system, there is still the need to elucidate some of the interactions and, thus, the zebrafish model can be used for that purpose as it respects the 3Rs concept and reduced time and costs. In view of the relevance of cannabinoids in the treatment and prevention of diseases, as well as the importance of the zebrafish animal model in elucidating the biological effects of new drugs, the aim of this study was to bring to light information on the use of the zebrafish animal model in testing C. sativa-based medicines.